Cone-to-Müller cell ratio in the mammalian retina: A survey of seven mammals with different lifestyle. (April 2019) - Lindenau, Wilhelm; Kuhrt, Heidrun; Ulbricht, Elke; Körner, Katrin; Bringmann, Andreas; Reichenbach, Andreas
Abstract: Mammalian retinal glial (Müller) cells are known to guide light through the inner retina to photoreceptors (Franze et al., 2007; Proc Natl Acad Sci U S A 104:8287–8292). It was shown that Müller cells transmit predominantly red-green and less violet-blue light (Labin et al., 2014; Nat Commun 5:4319). It is not known whether this optical function is reflected in the cone-to-Müller cell ratio. To determine this ratio in the retinas of mammals with different lifestyle, we evaluated the local densities of cones and Müller cells in the retinas of guinea pigs, rabbits, sheep, red deer, roe deer, domestic pigs, and wild boars. Retinal wholemounts were labeled with peanut agglutinin to mark cones and anti-vimentin antibodies to identify Müller cells. Wholemounts of guinea pig and rabbit retinas were also labeled with anti-S-opsin-antibodies. With the exceptions of guinea pig and pig retinas that had cone-to-Müller cell ratios of above one, the local densities of cones and Müller cells in the retinas of the species investigated were roughly equal. Because the proportion of S-cones is usually low (for example, 5.3% of all cones in the dorsal guinea pig retina expressed S-opsin), it is suggested that Müller cells are mainly coupled to M-cones. Exceptions are the ventral peripheries of guinea pig and rabbit retinas which are specialized areas with high S-cone densities. Here, up to 50% of Müller cells may be coupled to S-cones, and 40% of S-cones may be not coupled to Müller cells. Among the species investigated, the density of Müller cells in the central retina was inversely correlated with the axial length of the eyes. It is suggested that (with the exception of specialized S-cone areas) Müller cells support high acuity vision by predominant guidance of red-green light to M-opsin expressing cones. Highlights: Light transfer through Müller cells to single cones may improve acuity. Guinea pig and pig retinas have cone-to-Müller cell ratios of above one. Rabbits, sheep, red and roe deers and wild boars have ratios of about one. Müller cells are predominantly coupled to M-cones. In ventral guinea pig and rabbit retinas, 50% of Müller cells are linked to S-cones.